ANALISIS PEMBELIAN BIAYA BAHAN BAKU PRODUK ENGINE R-NR MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA PT. TOYOTA MOTOR MANUFACTURING INDONESIA PLANT 3 - Yulius Jatmiko Nuryatno; Fitra Aprilindo Sase; Alia Putri Maulida (JURNAL ILMIAH EDUNOMIKA, 2023)
The main raw material costs incurred by PT. Toyota Motor Manufacturing Indonesia Plant 3 Karawang to produce the R-NR engine is a large amount of expenditure because it is the main raw material for the production process. This study is intended to determine and analyze how the cost of ordering and using raw materials for Aluminum Ingots through the Economic Order Quantity (EOQ) method at PT. Toyota Motor Manufacturing Indonesia Plant 3 Karawang. The type of research applied in the following research is descriptive quantitative, namely the type of research aimed at explaining something using numerical research and carrying out data analysis through statistical procedures. The analytical method applied to the following research is the Economic Order Quantity (EOQ) research. The results of this study indicate that the EOQ method in the company can save the total cost of buying raw materials for Aluminum Ingots at PT. Toyota Motor Manufacturing Indonesia Factory 3.